Manajemen Sarana dan Prasarana untuk Efektivitas Layanan Administrasi Akademik di SMK Plus Darunnajah Maruyungsari - Desiana Afifah Rachmah; Nursiyah Mufarohah; Iis Rianti; Yeti Puspitasari (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2023)
This study aims to describe the implementation of facilities and infrastructure to supervise the planning of facilities and infrastructure for the effectiveness of academic administration services. This study usesqualitative research methods, the approach used is phenomenology. Sources of data taken through 3 people as informants. Data collection procedures include interview techniques, field observations and documentation studies. The data analysis used is Miles and Huberman analysis, namely data reduction, data presentation, and conclusion drawing. To test the validity used, the credibility test was carried out with the tringulation technique, transferability test, dependability, and confirmability.The results of the research findings are: (1) planning in the management of facilities and infrastructure for the effectiveness of academic administration services at SMK Plus Darunnajah Padaherang is carried out by the Deputy Principal (WKS) II Facilities and Infrastructure and is assisted by the Head of the Other Fields unit and approved by the Principal. (2) Implementation of Facilities and Infrastructure at SMK Plus Darunnajah Padaherang is carried out by all parties in SMK Plus Darunnajah Padaherang. In practice, the number of facilities and infrastructure is not met so that their utilization is not optimal. (3) supervision is carried out by all parties who use academic administrative facilities and infrastructure at SMK Plus Darunnajah. The supervision carried out by WKS II is not supported by a good inventory. So that planning for the future is not optimal, the management of facilities and infrastructure for the effectiveness of academic administration services at SMK Plus Darunnajah has been carried out and is in accordance with PERMEN DIKNAS No. 24 of 2007. However, the management of WKS II archives is not good and the number of existing facilities and infrastructure is not adequate due to limited funding.